PENDIDIKAN YANG MENDUKUNG PERKEMBANGAN SOSIAL, EMOSIONAL, DAN ETIS SISWA - Dearma Friend Damanik; Pebri Hot Marisi Silaen; Febri Martauli Hutabarat (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
Education plays a crucial role in shaping individuals who are socially adept, emotionally stable, and ethically grounded. This journal explores how education can support the social, emotional, and ethical development of students. By analyzing various strategies and approaches that have proven effective, this research aims to provide profound insights into the role of education in shaping holistic individuals. The discussed approaches include collaborative learning, empathy development, mental well-being education, and character education. Furthermore, the challenges and opportunities in implementing these approaches in the context of modern education are also thoroughly discussed. By understanding the importance of supporting the social, emotional, and ethical development of students, it is hoped that this journal can make a valuable contribution to stakeholders in the field of education.